Structural and biochemical basis for DNA and RNA catalysis by human Topoisomerase 3β - Xi Yang; Sourav Saha; Wei Yang; Keir C. Neuman; Yves Pommier (Nature Communications, 2022)
The authors revealed novel roles of catalytic residues and divalent metal ions for hsTOP3B, the human RNA topoisomerase, and demonstrated the structural elements that kinetically modulate the DNA and RNA topoisomerase activities of TOP3B.